İbnü’l-Cüneyd el-Huttelî ve el-Mahabbetü Li’llâh adlı eseri - Ulusoy, Tuğba (My University, 2025)
Hicrî 200 (816) yılında dünyaya gelen İbnü’l-Cüneyd el-Huttelî, aslen Horasan bölgesinin Huttel kasabasındandır; ancak hayatının büyük bir kısmını Bağdat ve Sâmerrâ'da geçirmiştir. Hadis ilmini tahsil etmek amacıyla Basra, Kûfe, Dımaşk ve Mısır gibi dönemin önemli ilim merkezlerine rihlelerde bulunmuştur. Kaynaklarda evlenmediği ve Yahyâ b. Maʿîn’in eleştirisinden sonra zâhidâne bir hayat tarzını benimsediği belirtilmektedir. Hem muhaddis hem de sûfî kimliğiyle öne çıkan Huttelî, hadis âlimleri tarafından güvenilir (sika) bir râvî olarak kabul edilmiştir. Başta Ahmed b. Hanbel olmak üzere birçok otoriteden hadis rivayet eden Huttelî’nin sekiz kadar eserinin adı geçmekle birlikte, bunlardan yalnızca biri hadis ve biri tasavvuf alanında olmak üzere iki eseri günümüze ulaşabilmiştir. Tezimizin temel inceleme konusunu da tasavvuf sahasında kaleme aldığı ve Allah sevgisi teması etrafında şekillenen ilk örneklerden biri kabul edilen el-Mahabbetü li’llâhi sübhâneh adlı eseri oluşturmaktadır. Tez, Giriş ve iki bölüm olmak üzere üç bölümden oluşmaktadır. Giriş bölümünde, Huttelî’nin yaşadığı dönemin ilmî ve siyasî yapısı ele alınarak, bu ortamın onun ilmî kişiliği ve düşünce dünyasına etkisi analiz edilmiştir. Birinci bölümde, Huttelî’nin hadis ilmindeki yeri ortaya konmaya çalışılmış; bu çerçevede hocaları, öğrencileri, ricâl bilgisi, hadis rivayetindeki tutumu ve hakkında zikredilen cerh-taʿdîl değerlendirmeleri sistemli biçimde incelenmiştir. İkinci bölümde ise, el-Mahabbe'de geçen 15 müsned merfû hadis sened ve metin açısından tahlil edilmiştir. Bu kapsamda, hadislerin temel kaynaklardaki yerleri belirlenmiş; râvîlerin güvenilirlik durumları, senedlerdeki kopukluklar ve metinlerdeki muhteva, lafız farklılıkları ve olası şâzlıklar değerlendirilmiştir. Böylece Huttelî’nin hadis ilmine katkısı ile eserinin ilmî değeri ortaya konulmaya çalışılmıştır.

Born in the year 200 AH (816 CE), Ibn al-Junayd al-Khuttalī originally hailed from the town of Khuttal in the region of Khurasan; however, he spent the majority of his life in Baghdad and Sāmarrā. He undertook scholarly journeys (rihlas) to major centers of learning of his time—such as Basra, Kufa, Damascus, and Egypt—in pursuit of the science of hadith. The sources indicate that he never married and, following the criticism of Yahyā b. Maʿīn, adopted an ascetic way of life. Distinguished by both his identity as a muhaddith and a sūfi, al-Huttalī was recognized by hadith scholars as a reliable transmitter. Although Khuttalī transmitted hadiths from many authorities, most notably Ahmad ibn Hanbal, seven works are attributed to him; however, only two of these have survived to the present day—one in the field of hadith and the other in the field of Sufism. The primary subject of our thesis is al-Khuttalī’s work in the field of Sufism titled al-Mahabbatu li’llāhi subhānah, which is considered one of the earliest examples structured around the theme of love for God. The thesis consists of three parts: an Introduction and two chapters. In the Introduction, the intellectual and political context of the period in which al-Khuttalī lived is examined, and the influence of this environment on his scholarly identity and intellectual outlook is analyzed. The first chapter aims to establish al-Khuttalī’s place in the field of hadith studies; in this context, his teachers, students, biographical evaluations (rijāl), his approach to hadith transmission, and the critiques and endorsements (jarh and taʿdīl) made about him are examined systematically. In the second chapter, fifteen musnad marfūʿ hadiths found in al-Mahabbah are analyzed in terms of both their chains of transmission and their texts. Within this framework, the presence of these hadiths in the major sources is identified; the reliability of the transmitters, possible discontinuities in the chains, and aspects such as the content, variations in wording, and potential shādhdh elements in the texts are assessed. In doing so, the study seeks to highlight al-Khuttalī’s contribution to the science of hadith and the scholarly value of his work.
Keywords: Baghdad; Bağdat; Divine Love; Hadis; HadisHadith; Hadith; Huttelî; Ibn al-Junayd; İbnü'l-Cüneyd; İbnü’l-Cüneyd el-Huttelî, H. 200 (816)-?; Khuttalī; Mahabbetullah; Metinler; Muhaddis; Muhaddith; Tahrîc; Takhrij; Texts